Pemikiran Pendidikan al-Mawardi dan Relevansinya dengan Nilai-Nilai Pendidikan Islam antara Batasan Guru dengan Murid - Ridwan Ridwan (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2018)
Al-Mawardi require that a teacher is sincere carrying out its duties. Educating and teaching should be oriented to higher purpose, to teach and educate, a scientific activity that has value and a high position, which is not aligned with the material. Sincerity and awareness of a teacher is the awareness of importance of tasks, so it will be driven to achieve maximum results. A teacher will perform his duties in a professional manner, with characterized by some attitudes. First, always prepare everything that was needed to support the teaching and learning process. Second, a teacher who will act exactly the sincere promise and the completion of his duties. Third, the use of spare time will be directed to his professional interests. Fourth, perseverance and tenacity in work. Teachers who are sincere will realize the importance of perseverance and tenacity to work in achieving its tasks. Fifth, creativity and innovation have a high, arising from awareness of the increasing demands and challenges of education prospects. Then in the process of learning certainly can not be separated with Islamic values that must be planted in a se guru as well as must have attitudes, tawadhu, or humble aqid, exemplary, piety of god is omnipotent.